CVaR sensitivity with respect to tail thickness - Stoyan V. Stoyanov; Svetlozar T. Rachev; Frank J. Fabozzi (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2011)
We consider the sensitivity of conditional value-at-risk (CVaR) with respect to the tail index assuming regularly varying tails and exponential and faster-than-exponential tail decay for the return distribution. We compare it to the CVaR sensitivity with respect to the scale parameter for stable Paretian, the Student's t, and generalized Gaussian laws and discuss implications for the modeling of daily returns and marginal rebalancing decisions. Finally, we explore empirically the impact on the asymptotic variability of the CVaR estimator with daily returns which is a standard choice for the return frequency for risk estimation.
urn:nbn:de:swb:90-232402
Keywords: 330; fat-tailed distributions; regularly varying tails; conditional value-at-risk; marginal rebalancing; asymptotic variability